The role of sleep in neuromuscular disorders - Corrado I. Angelini; Carl Ansevin; Gabriele Siciliano (Frontiers in Neurology, 2023)
Sleep represents a major frontier both in clinical myology and as a new possibility for delivering treatment to neuromuscular patients since various neuromuscular cases present a variable degree of disordered sleep and such conditions should be diagnosed and prevented, i.e., sleep apnea and hypoxemia. These sleep disorders are present in dystrophinopathies and in various types of limb-girdle muscular dystrophies (LGMD). Excessive daytime sleepiness (EDS) is found in patients affected by spastic paraparesis or cerebellar ataxia but is rather common in both myotonic dystrophy type 1 and 2, and the correction of sleep disorders is therefore important to improve their daily quality of life (QoL) and consequent daily functioning. Other types of sleep dysfunction such as insomnia, a reduction in rapid eye movement (REM) sleep, loss of normal REM, or sleep-disordered breathing are found in other disorders including myasthenia, ataxias, spastic paraparesis, Charcot–Marie–Tooth disease, and neurogenic disorders, including polyneuropathies, and need appropriate treatment. Research done on this topic aims to incorporate a variety of nuances in metabolic disorders such as those in late-onset Pompe disease and are such as those in late-onset Pompe disease who are susceptible to enzyme replacement therapy (ERT). The overarching goal is to explore both the diagnosis and methodology of sleep-related problems in both genetic and acquired neuromuscular disorders. We also review the type of available treatment opportunities utilized to improve neuromuscular patients’ QoL.